2017
DOI: 10.1248/cpb.c17-00568
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorinated Cobalt(III) Porphyrin Complex for Hydroalkoxylation of Alkynes

Abstract: A fluorinated cobalt(III) porphyrin complex [Co(TPFPP)- (Fig. 1). This method compares well with the earlier procedures catalyzed by Hg, 6,7) Pd, [8][9][10] Pt, 9,11,12) Au, [13][14][15][16][17][18][19][20][21][22] Ir [23][24][25][26] and Zn. 27)The active pentafluorophenylated Co III catalyst 1a was developed by structural modification of 1b used previously for alkyne hydration 2) (Fig. 1). Reaction of tetrakis(pentafluorophenyl) porphyrin (H 2 TPFPP) and cobalt(II) acetate 28) followed by aerobic oxidation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…During the course of our recent study seeking efficient methods for catalytic hydration of unsaturated organic compounds, we found that the use of palladium chloride and carboxamide allows the hydration of acetone cyanohydrin ( 1a ). The conversion of nitriles to amides by palladium chloride and acetamide was initially described by Maffioli et al as a reverse reaction of the dehydration of amides to nitriles .…”
mentioning
confidence: 99%
“…During the course of our recent study seeking efficient methods for catalytic hydration of unsaturated organic compounds, we found that the use of palladium chloride and carboxamide allows the hydration of acetone cyanohydrin ( 1a ). The conversion of nitriles to amides by palladium chloride and acetamide was initially described by Maffioli et al as a reverse reaction of the dehydration of amides to nitriles .…”
mentioning
confidence: 99%
“…It is worth mentioning that the reaction is specific to water. Acetophenone was formed in the system, and no evidence of hydroalkoxylation reaction products was detected 35 …”
Section: Resultsmentioning
confidence: 96%
“…Ushimaru et al . (61) reported that the fluorinated Co(III) porphyrinoid, CoTPPF 20 ‐NTf 2 ·2C 2 H 5 OH (where Tf = CF 3 SO 2 ) can catalyze the conversion of both aliphatic and aromatic terminal alkynes into acetals in excellent yield. These can then be further functionalized by attacking the acetals with desired nucleophiles.…”
Section: Materials Applicationmentioning
confidence: 99%